Child Avoidance of Anxiety-Provoking Situations in the Classroom and Teacher Accommodation. Issue 1 (20th June 2023) - Ginsburg, Golda S.; Pella, Jeffrey E.; DeVito, Anneliese; Chan, Grace
Abstract: This study examined: (1) school-based avoidance among students with problematic anxiety, (2) teachers' levels of accommodation of avoidant behaviour, and (3) the relation between teacher accommodation and student avoidance and anxiety. Participants included 31 elementary school students with problematic anxiety (mean age = 7.7 years; range 5–11; 58% female; 71% White) and their teachers (mean age = 41.1 years; 100% female; 100% White). Children completed interviews about their anxiety, and teachers reported on students' avoided situations and completed a questionnaire about their own use of accommodation. Results indicated that the most commonly avoided situations involved individual and group academic performance (e.g., reading aloud in front of class). All teachers engaged in some form of accommodating behaviour more than one day a week (e.g., assisted a student in avoiding things that might make him/her more anxious), and teachers who reported engaging in more accommodating behaviours had students with higher avoidance and anxiety. Findings suggest that additional training and research on teachers' behaviours that maintain and/or reduce anxiety via reducing accommodating behaviours appears warranted.